1996
DOI: 10.1144/gsl.sp.1996.106.01.23
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic evolution of the Bantimala Complex, South Sulawesi, Indonesia

Abstract: The Bantimala Complex of South Sulawesi, Indonesia is an assemblage of northeastdipping tectonically stacked slices. The slices consist mainly of high pressure metamorphic rocks, radiolarian chert, breccia, sandstone and shale, and melange. In order to understand the tectonic evolution of the Bantimala Complex, we have investigated the lithology, age, stratigraphy, structure and relationships of the components. The K-Ar ages of high P-low T metamorphic rocks suggest that an oceanic plate subducted beneath the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 11 publications
3
66
0
2
Order By: Relevance
“…1a). The study area (South Sulawesi) predominantly comprises sandstone, shale, chert, basalt, dunite, lherzolite, serpentinite, and various metamorphic rocks ranging from low grade to eclogite-facies conditions (Sukamto, 1982;Wakita et al, 1994Wakita et al, , 1996Miyazaki et al, 1996;Parkinson et al, 1998) (Fig. 1b).…”
Section: Geological Outlinementioning
confidence: 99%
See 2 more Smart Citations
“…1a). The study area (South Sulawesi) predominantly comprises sandstone, shale, chert, basalt, dunite, lherzolite, serpentinite, and various metamorphic rocks ranging from low grade to eclogite-facies conditions (Sukamto, 1982;Wakita et al, 1994Wakita et al, , 1996Miyazaki et al, 1996;Parkinson et al, 1998) (Fig. 1b).…”
Section: Geological Outlinementioning
confidence: 99%
“…1b). The Bantimala Complex is a tectonic stack of slices mainly consisting of various sedimentary rocks, ultramafic rocks, metabasites, and metapelites with ages ranging from Jurassic to middle Cretaceous (Sukamto, 1982;Wakita et al, 1994Wakita et al, , 1996Miyazaki et al, 1996;Parkinson et al, 1998). The metamorphic rocks mainly occur within a mélange unit.…”
Section: Geological Outlinementioning
confidence: 99%
See 1 more Smart Citation
“…The complex is believed to be equivalent and has been named the Bantimala Tectonic Complex (Sukamto, 1982 Previously, Wakita et al (1994bWakita et al ( , 1996 reported middle Cretaceous (Albian to Cenomanian = 108 -92 Ma) radiolarians extracted from chert and siliceous shale of the Bantimala Complex. The two differences that related on radiolarian occurrence in the Barru Complex and the Bantimala Complex are radiolarians age and radiolarian-bearing rocks.…”
Section: Discussionmentioning
confidence: 99%
“…Of the two exposures, the larger (Bantimala Complex) is the better known. The detailed geology of the Bantimala Complex has been investigated by Sukamto (1975Sukamto ( , 1978Sukamto ( , 1982Sukamto ( , 1986, Hasan (1991) and Wakita et al (1994bWakita et al ( , 1996. Sukamto (1982) established that the older rocks, which unconformably overlain by Late Cretaceous Balangbaru Formation -flysch type sedimentary rocks, as a mass named the Bantimala Tectonic Complex.…”
Section: Geologic Settingmentioning
confidence: 99%